The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1155/2016/5123519
|View full text |Cite
|
Sign up to set email alerts
|

Miconia sp. Increases mRNA Levels of PPAR Gamma and Inhibits Alpha Amylase and Alpha Glucosidase

Abstract: Diabetes mellitus is a public health problem worldwide. For this reason, ethanolic extract of Miconia sp. from Oaxaca, Mexico, was selected in search of an alternative against this disease. The effect of Miconia sp. on mRNA expression of PPARγ on cell line 3T3-L1, its effect on alpha amylase and alpha glucosidase, lipid accumulation during adipogenesis, and cell viability on VERO cells were evaluated. The mRNA levels of PPARγ increased on 1.393 ± 0.008 folds, lipid accumulation was increased by 29.55% with Mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
6
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 24 publications
3
6
0
1
Order By: Relevance
“…Our finding is in accordance with earlier reports that showed that some medicinal plant extracts have more potent α -glucosidase inhibitory activities than powerful synthetics inhibitors such as acarbose [3234]. Also, the results are in line with a study performed on another species of Cistus genus ( Cistus laurifolius L.) that showed that ethanolic extract of this plant is a potent inhibitor of α -glucosidase (IC 50 = 6.3  μ g/mL) and has a remarkable and dose-dependent inhibitory effect on α -amylase and also improves hyperglycemia in type 2 diabetic rats [35].…”
Section: Resultssupporting
confidence: 94%
“…Our finding is in accordance with earlier reports that showed that some medicinal plant extracts have more potent α -glucosidase inhibitory activities than powerful synthetics inhibitors such as acarbose [3234]. Also, the results are in line with a study performed on another species of Cistus genus ( Cistus laurifolius L.) that showed that ethanolic extract of this plant is a potent inhibitor of α -glucosidase (IC 50 = 6.3  μ g/mL) and has a remarkable and dose-dependent inhibitory effect on α -amylase and also improves hyperglycemia in type 2 diabetic rats [35].…”
Section: Resultssupporting
confidence: 94%
“…At the best of our knowledge, there are any study carried out on antidiabetic effects of AIEO. Furthermore, our findings are in line with previous studies that have proven that some medicinal plants have more potent inhibitory activities than the reference compound such as acarbose 37,38 . Moreover, our results are in agreement with other studies that found that the aqueous extract of A iva decreased blood glucose levels in diabetic rats compared to the control group 39,40 .…”
Section: Resultssupporting
confidence: 93%
“…Nonetheless, this potential was more portrayed in α -amylase activity as T. catappa leaf extracts exhibited a better inhibitory potential than acarbose. This was corroborated by various studies that have previously reported a higher inhibitory potential of medicinal plant extracts than acarbose [16, 18, 19]. It was also noteworthy that our extracts had better α -glucosidase and α -amylase inhibitory activities than those reported for Nicotiana tabacum and Calotropis procera leaf extracts [20, 21].…”
Section: Discussionsupporting
confidence: 88%